2013
DOI: 10.3928/00485713-20130605-11
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Service Dog Training in the Treatment of Combat-Related PTSD

Abstract: Valerie, a golden retriever, demonstrates her ability to connect with a Marine at the National Intrepid Center of Excellence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Positive interactions between humans and dogs, for example, have been proven to increase levels of oxytocin in both humans and dogs (Nagasawa et al, 2015). This has been found to cause a more positive mood, decreased negative emotions, and increased perceived welfare in humans (Beetz, Uvnäs-Moberg, Julius, & Kotrschal, 2012;Yount, Ritchie, St Laurent, Chumley, & Olmert, 2013). Moreover, companion animals act as social facilitators between humans, reducing the risk of social isolation (Banks & Banks, 2002;McNicholas & Collis, 2000;Wood, Giles-Corti, & Bulsara, 2005).…”
Section: The Influence Of Dogs On Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive interactions between humans and dogs, for example, have been proven to increase levels of oxytocin in both humans and dogs (Nagasawa et al, 2015). This has been found to cause a more positive mood, decreased negative emotions, and increased perceived welfare in humans (Beetz, Uvnäs-Moberg, Julius, & Kotrschal, 2012;Yount, Ritchie, St Laurent, Chumley, & Olmert, 2013). Moreover, companion animals act as social facilitators between humans, reducing the risk of social isolation (Banks & Banks, 2002;McNicholas & Collis, 2000;Wood, Giles-Corti, & Bulsara, 2005).…”
Section: The Influence Of Dogs On Ptsdmentioning
confidence: 99%
“…A specific situation in which this might happen is when someone with PTSD is suffering a flashback of the event(s) that triggered the PTSD. While experiencing such flashbacks, the presence of a dog can help the person to focus on the present, reminding them that the danger is no longer there (Yount et al, 2013) The specialized training of a service dog may further strengthen this association, as it can be trained to actively seek its handler's attention, strengthening the re-orienting effect.…”
Section: The Influence Of Dogs On Ptsdmentioning
confidence: 99%
“…Reductions in startle response and depression, as well as improvements in emotional regulation have been reported amongst veterans involved in service dog training programs (Steele, ; Yount et al, ). This is consistent with our study as participants stated that their service dog assisted them in regulating their mood by reducing anxiety and anger.…”
Section: Discussionmentioning
confidence: 95%
“…Animal assisted interventions can lead to overall reductions in anxiety and depression (O’Haire, Guerin, & Kirkham, ), which can result in a reduction in the use of medication. Reports of decreased medication use, especially amongst service dog users with PTSD, has been documented (Steele, ) and a reduction in the use of pain medication has been reported amongst participants in a service dog training program(Yount et al , ). Some participants in our study reported decreased use of medication, particularly Diazepam (Valium).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation